(untitled) (La U Investiga, 2023)
Mitochondrial encephalomyopathy, lactic acidosis, and stroke-like syndrome, also called MELAS, is a relatively unknown medical condition; however, it is the most common mitochondrial disease. This condition is hereditary, multisystemic, and progressive. We present the case of a 14-year-old adolescent diagnosed with MELAS at HSVP (San Vicente de Paúl Hospital) based on the clinical criteria of the MELAS Study Group Committee in Japan - 2012. The patient has been experiencing headaches, vomiting, and generalized tonic-clonic seizures since the age of 10. At the age of 13, she developed bilateral sensorineural hearing loss, and at 14, she experienced focal clonic seizures, hyperlactatemia, and an image of a left temporo-parietal infarction on cerebral magnetic resonance imaging. From our perspective, MELAS syndrome is still poorly understood, and the diagnosis is often delayed. This syndrome primarily affects the neurological system, leading to disability and high mortality rates. This article presents a clinical case that invites to know and learn more about this pathology.